Suscetibilidade de cultivares de café arábica a Hypothenemus hampei (coleoptera:curculionidae) na região sul de Minas Gerais - Alves, Müller Cesar (2021)
The coffee berry borer (Hypothenemus hampei) is considered one of the main pests that attack the coffee culture in Brazil and in the world, being responsible for quantitative and qualitative losses in the production and quality of the beverage. The use of resistant cultivars is one of the main methods of control in Integrated Pest Management programs. However, there is little information on the resistance and susceptibility of commercial Arabica coffee cultivars available in the market to the coffee borer, thus, there is a need to evaluate the coffee borer infestation in new cultivars in order to to classify them in terms of resistance/susceptibility and dissemination to the scientific community and producers. This work aimed to evaluate, under field conditions in Lavras, southern Minas Gerais, the resistance/susceptibility of commercial Arabica coffee cultivars to coffee borer. The experiment was carried out in the cultivars panel of INCT-Café, UFLA, Lavras, MG. The resistance of arabica coffee to coffee borer was evaluated in plots arranged in three randomized blocks, with 20 commercial cultivars and 2 clones. The plots were constituted by 10 plants in a row and the useful area of the plot represented by the six central plans. Sampling of the coffee borer infestation in the fruits will be carried out every two weeks in branches of the upper and middle thirds of the plants. Fruits from the thirds of the plants were also collected and taken to the laboratory, where they were opened to verify the presence of larvae and adults inside the fruits. In addition, the perforation damage caused by the drill with the characteristics of Periphery, Middle, Seed and Dirty Brocade was evaluated. Only a few cultivars tested in this study showed statistically differentiated susceptibility, and Siriema stood out with high susceptibility to coffee borer infestation and medium maturity. Cultivars Aranãs Rh, Acauã, Arara, IPR 103, IPR 100 and IPR 102 showed low susceptibility to pest attack and medium maturity.